Molecular Adaptations to Concurrent Training - de Souza, E. O.; Tricoli, V.; Roschel, H.; Brum, P. C.; Bacurau, A.V. N.; Ferreira, J.C. B.; Aoki, M. S.; Neves-Jr, M.; Aihara, A. Y.; da Rocha Correa Fernandes, A.; Ugrinowitsch, C. (International Journal of Sports Medicine, 2013)
This study investigated the chronic effects of concurrent training (CT) on morphological and molecular adaptations. 37 men (age=23.7±5.5 year) were divided into 4 groups: interval (IT), strength (ST) and concurrent (CT) training and a control group (C) and underwent 8 weeks of training. Maximum strength (1RM) and muscle cross-sectional area (CSA) were evaluated before and after training. Muscle samples were obtained before the training program and 48 h after the last training session. VO2max improved in 5±0.95% and 15±1.3% (pre- to post-test) in groups CT and IT, respectively, when compared to C. Time to exhaustion (TE) improved from pre- to post-test when compared to C (CT=6.1±0.58%; IT=8.3±0.88%; ST=3.2±0.66%). 1RM increased from pre-to post-test only in ST and CT groups (ST=18.5±3.16%; CT=17.6±3.01%). Similarly, ST and CT groups increased quadriceps CSA from pre-to post-test (6.2±1.4%; 7.8±1.66%). The p70S6K1 total protein content increased after CT. The ST group showed increased Akt phosphorylation at Ser473 (45.0±3.3%) whereas AMPK phosphorylation at Thr172 increased only in IT group, (100±17.6%). In summary, our data suggest that despite the differences in molecular adaptations between training regimens, CT did not blunt muscle strength and hypertrophy increments when compared with ST.
Keywords: maximum dynamic strength; muscle hypertrophy; interval training